Causal Relationship between Renewable Energy Consumption and Unemployment in Nigeria: Evidence from Toda and Yamamoto Causality Technique - Musa, Kabiru Saidu; Maijama’a, Rabiu (Energy Economics Letters, 2020)
The paper examines the causal association among renewable energy consumption and unemployment in Nigeria for the sample of 1991-2015 periods via the technique of Toda and Yamamoto causality. The outcome of the long-run causality specifies that bidirectional causality exist between renewable energy consumption and unemployment; foreign direct investment and renewable energy consumption; investments and renewable energy consumption; credit to private sector and renewable energy consumption; foreign direct investments and investments; credit to private sector and investments with unidirectional causality among investments and unemployment; credit to private sector and unemployment. This suggests that higher consumption of energy from renewable sources will go a long way in providing the long-lasting solution to the problems of unemployment in the country. It is therefore recommended that Nigerian government should put more efforts on increasing production and consumption of energy from renewable source as it has the tendency of decreasing the rate of unemployment in the long-run and barriers in the form of higher cost of acquisition and taxes on the production and consumption of energy from the renewable sources should be completely eliminated in order to increase the rate of investments in renewable energy technologies and subsequently create employments.